The Influence of Innovation and Competence on Employee Performance at Coffee Shops in Blora Regency - Siti Miratun Nafisah; Lia Kian (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study examines the relationship between innovation, competence, and employee performance in coffee shop businesses in Blora Regency, with additional attention to revenue performance trends from 2022 to 2024. The empirical findings indicate a consistent decline in revenue across the observed period, reflecting structural challenges driven by increasing market saturation, intensified competition, and shifting consumer preferences toward experience-based consumption. These conditions highlight the importance of internal organizational factors in sustaining business performance. The study shows that innovation plays a significant role in enhancing employee performance through improvements in service delivery, operational systems, digital integration, and customer engagement strategies. Employees in more innovative environments demonstrate higher adaptability and better service quality. In addition, employee competence, including knowledge, skills, and work attitudes, is found to be essential in ensuring service consistency and customer satisfaction. The findings further indicate that innovation and competence function in a complementary and mutually reinforcing manner, where neither variable alone is sufficient to optimize performance. Their integration significantly contributes to improved employee effectiveness and business sustainability in highly competitive SME service environments. Therefore, strengthening both innovation and competence is crucial for improving long-term competitiveness and resilience in coffee shop businesses.